Movement Preparation and Down Syndrome: The Costs and Benefits of Advance Information - Le Clair, David (My University, 1994)
This study attempts to resolve to what extent individuals with Down syndrome benefit from advance information provided visually, versus the same information provided verbally when performing a manual aiming task. Adults with Down syndrome and undifferentiated developmental handicaps, as well as control subjects without a developmental handicap, performed manual aiming movements to targets 10.5 cm. away. On a particular trial, subjects were cued about the specific movement either visually or verbally. The cue provided either 50% or 80% certainty. Nonhandicapped control subjects initiated and completed their manual aiming movements more quickly than subjects with mental handicaps. As well, individuals with Down syndrome were found to be slower and more variable in reaction time than individuals in the other mentally handicapped group when valid information was provided verbally but not when the cue was provide visually. These results provide support for the Elliott and Weeks (1990) model of biological dissociation. Specifically, the atypical hemispheric lateralization for speech perception exhibited by individuals with Down syndrome results in a disruption in communication between functional systems responsible for the processing of verbal langauge, and the organization of complex movement.
Keywords: movement preparation; Down syndrome; cost and benefit; advance information